2015
DOI: 10.1063/1.4921438
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of Cu2BIICIVX4VI magnetic quaternary semiconductor compounds with tetragonal stannite type structure

Abstract: A comparative study of the Raman spectra of Cu2BIICIVS4VI and Cu2BIICIVSe4VI(where B = Mn or Fe) magnetic quaternary semiconductor compounds with stannite-type structure (I4¯2m) has been done. Most of the fourteen Raman lines expected for these materials were observed in the spectra. The two strongest lines observed have been assigned to the IR inactive A11 and A12 stannite modes that originated from the motion of the S or Se anion around the Cu and CIV cations remaining at rest. The shift in the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…Because for α‐Cu 2 ZnGeTe 4 the three A ‐symmetry modes expected involve only the motion of the Te anion at 8 g position (see Table ), their vibrational frequencies can be estimated from the model by the ST quaternaries mentioned above by assuming that the frequency of these three modes in increasing energy depend only of Zn–Te, Cu–Te, and Ge–Te bond stretching force constants, respectively. This yields for the frequencies of these A ‐symmetry KS modes the values 122, 124, and 141 (± 5) cm −1 in good agreement with the three strongest peaks observed in the present Raman spectrum at 116, 119, and 139 cm −1 . The remaining Raman lines at 81, 89, 97, and 263 cm −1 can be tentatively ascribed to B or E ‐symmetry kesterite modes.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Because for α‐Cu 2 ZnGeTe 4 the three A ‐symmetry modes expected involve only the motion of the Te anion at 8 g position (see Table ), their vibrational frequencies can be estimated from the model by the ST quaternaries mentioned above by assuming that the frequency of these three modes in increasing energy depend only of Zn–Te, Cu–Te, and Ge–Te bond stretching force constants, respectively. This yields for the frequencies of these A ‐symmetry KS modes the values 122, 124, and 141 (± 5) cm −1 in good agreement with the three strongest peaks observed in the present Raman spectrum at 116, 119, and 139 cm −1 . The remaining Raman lines at 81, 89, 97, and 263 cm −1 can be tentatively ascribed to B or E ‐symmetry kesterite modes.…”
Section: Resultssupporting
confidence: 88%
“…For Cu 2 GeTe 3 , to the best of our knowledge, no Raman studies have been reported. However, since for the Cnormalu2normalBIVnormalX3VI ternary compounds main Raman peaks observed are related to vibrations of the X VI anion , it is expected that Raman spectrum for Cu 2 SnTe 3 should be similar to that of Cu 2 GeTe 3 . Thus, lines at 123 and 142 cm −1 of the present spectrum which coincides with those of the main lines reported for Cu 2 SnTe 3 are tentatively assigned to Cu 2 GeTe 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra of the pure‐CZTSSe absorber and CMZTSSe thin film excited at 514 nm are shown in Figure S3, Supporting Information. It is observed that three most intense Raman peaks are centered at around 166, 189, and 228 cm −1 , respectively, which are indexed as the Raman characteristic peaks of CZTSe or CMTSe . Obviously, the main peaks shift to lower wavenumber as Zn is substituted partially by Mn, which is because the three intense Raman peaks of CMTSe are located in the lower wavenumber than those of CZTSe.…”
Section: Resultsmentioning
confidence: 98%
“…This will directly influence the energy of the phonons, which will lead to a shift of Raman peaks while maintaining the overall spectrum pattern. Taking this into account, a typical Raman spectrum of any kesterite-type quaternary compound can be predicted [42]. On the other hand, using excitation wavelengths close to the resonant conditions can have a significant effect on the fingerprint of Raman spectra.…”
Section: Fingerprint Raman Spectramentioning
confidence: 99%